School Leadership Styles and Performance Appraisal Matter to Enhance Job Satisfaction: An Empirical Study among Secondary School Teachers in Pakistan - Sabir, Fozia; Hussin, Fauzi (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of this study is to investigate the effect of school leadership styles and performance appraisal on job satisfaction. A Cross sectional based on the quantitative research design was administered. The population of the study was secondary school teachers from Punjab, Pakistan. 279 teachers were selected as a sample of the study. Stratified random sample technique was adopted to select the sample from six divisions in Punjab, Pakistan. Standardized questionnaires were used according to the variables of the study whereas SPSS-25 was used to analyze the data. The findings of this study show there was a moderate effect of school leadership styles and performance appraisal on job satisfaction. The research will be helpful for the education leaders to adopt the new techniques for the enhancement of job satisfaction of the teachers for the development of education sector.